From the Evolution of the Waste Management System in Panyu District, Guangzhou City: Examining the Relationship between Public Participation and Institutional Reform - SO, Chun Hei (South Asian Journal of Social Sciences and Humanities, 2025)
The waste problem in major cities in mainland China is severe, causing significant challenges  for local governments. Faced with such a vast amount of waste, local governments often opt  for incineration as a primary disposal method. However, incineration brings various issues to  local residents, and the government's rigid enforcement has led to public backlash. Public  dissatisfaction with government policies has driven efforts to challenge the absolute authority  of decision-makers over the system. Various forms of public participation have emerged, and  in the process of reforming the waste management system in Panyu District, Guangzhou, it is  evident that public participation has provided significant space and impetus for institutional  change. This study examines the relationship between public participation and institutional  reform, observing how it prompts the government to alter established systems. In the context  of mainland China’s authoritarian regime, where public activities are not entirely free, notable  achievements have still been made. The paper begins with a literature review, followed by a  detailed exploration of the public’s resistance to the waste management system in Panyu  District, Guangzhou, and the government’s responses, assessing whether public participation  has driven institutional changes.
Keywords: Public Participation; Waste; China; Guangzhou; Panyu; Institutional Reform